Pigeon Point - Dolly, M. (Mike Roberts, California,United States of America;Distributed by M.Jolly,[Trinidad and Tobago], 2011)
Description printed on the back of the postcard: "Pelicans also enjoy a "sea bath" at Pigeon Point, Tobago." This postcard, number C5810, is addressed to Master R. Ribelin of New Jersey, United States of America and affixed is a 12 cents Trinidad and Tobago postage stamp.
Colour: Coloured; Style: Landscape; Other: Unbordered, Divided
Keywords: Trinidad and Tobago; Postcards; Pelicans--Trinidad and Tobago; Beaches--Trinidad and Tobago; Trinidad and Tobago; Coconut palm--Trinidad and Tobago; Seashore--Trinidad and Tobago; Coasts--Trinidad and Tobago; [1965]